Ant Species Composition Collected by Pan Traps in a Rehabilitated Coal Mining Area in Sawahlunto City, West Sumatra - Tasman, Ratna Juwita; Nurdin, Jabang; Herwina, Henny; Jasmi, Jasmi; Janra, Muhammad Nazri; Satria, Rijal (Universitas Andalas, 2024)
Pan traps is a popular technique for determining the diversity of pollinating insects in different settings. These traps are effective for field use and can quickly produce sample data because they are simple to operate and don't require any specific equipment to be deployed. Pan traps, however, also catch a variety of non-pollinator insects in addition to pollinating insects. In this study, the Pan traps methods were used in three different habitat types: rice-field, Acacia agroforestry and secondary forest on reclaimed coal mining site. Fourteen members of the Formicidae family with 11 species, 9 genera, 8 tribes, and 3 subfamilies were found from all of the combined traps. The most common species, with four records, was Camponotus arrogans, which was regularly found in all types of habitat. With 9 species and 14 individuals, blue pan traps caught the greatest diversity of ant species, while yellow pan traps were the least successful with one species and one individual. Comprehending the variables that impact ant diversity and abundance in various habitat types, as well as their interactions with the environment, can yield significant insights on the quality of habitats and function as markers of environmental alterations. This information is essential for the management of habitats and conservation initiatives.